Measurement of trypanotolerance criteria and their effect on reproductive performance of N'Dama cattle - Trail, J.C.M.; D'Ieteren, G.D.M.; Murray, M.; Ordner, G.; Yangari, G.; Collardelle, C.; Sauveroche, B.; Maille, J.C.; Viviani, P. (Elsevier, 1993)
Evaluates in detail how environmental and stress factorts affect trypanosome infection in N'Dama cows and their calves, the linkages with curative drug treatment given under the management regime prevailing, the linkages with anaemia control as measured by packed red cell volume (PCV), and the resultant influences on animal performance. Major findings were that over the period from calf birth to weaning, while calves and their dams grazing together had similar numbers of trypanosome infections detected, the Trypanosoma vivax : T. congolense rations were very different: 1:0.7 in calves and 1:2.8 in cows. This indicated that some ability to control the development of parasitaemia following T. vivax infection might be being acquired, from weaning onwards. Table 1 summarizes the data on trypanosome infection, curative drug treatment, PCV value and performance trait levels in the 458 pre-weaner calves, the 458 lactating cows and the 1028 cow-year reproduction records available over the 5-year period. These are the actual overall infection rates recorded, the levels of curative drug treatments required and the PCV values, calf growth and cow calving rates achieved.